Crosslinked polyolefin elastomer foam
By combining polyethylene/α-ene copolymer or polyolefin block copolymer with ethylene crosslinked polymer containing epoxy groups, and using chemical foaming agents and active agents, crosslinked polymer foams with good thermal stability are prepared, which solves the problem of foam cell collapse when the foam is thermally aged at high temperature in the prior art, and the high temperature thermal stability and mechanical properties of the foam are improved.
Patent Information
- Application Number
- JP2022539051
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2020-12-21
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-12-21
AI Technical Summary
In the prior art, when the polypropylene copolymer used to prepare artificial leather is thermally aged at high temperature, the foam cell is prone to collapse, resulting in surface deformation and lacks good thermal stability.
A crosslinked polymer foam with good thermal stability is prepared by combining polyethylene/α-ene copolymer or polyolefin copolymer with ethylene crosslinked polymer containing epoxy groups.
The good thermal stability of polypropylene copolymer foam above 150°C is achieved, the collapse of foam cell and surface deformation is avoided, and the mechanical and thermal properties of the foam are improved.
Smart Images

Figure 0007654668000003 
Figure 0007654668000004 
Figure 0007654668000005
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to International Patent Application No. PCT / CN2019 / 127943, filed December 24, 2019, the entire disclosure of which is incorporated herein by reference.
[0002] FIELD OF THEINVENTION FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to polyolefin foams, and more particularly to crosslinked foams comprising a polyolefin elastomer and an epoxy-containing ethylene interpolymer. [Background technology]
[0003] Artificial leather is used as a replacement for natural leather in a wide range of applications, including footwear, apparel, furniture, automobiles, and other applications. Heat resistance can be an important factor in at least some of these applications. For example, car seat applications require that the artificial leather be free of foam cell collapse and leather surface warping after heat aging at temperatures above 100° C. for a given period of time.
[0004] Although propylene-based copolymers have been used to prepare artificial leather, the compositions have a narrow foaming window. Thus, there is a need for alternative polyolefin foams that have good foaming and heat resistance properties. Summary of the Invention
[0005] The embodiments of the present disclosure fulfill this need by providing a polyolefin elastomeric crosslinked foam that exhibits good heat resistance above 150°C. According to one or more embodiments herein, the foam is formed from a composition including at least 50% by weight of an ethylene / alpha-olefin copolymer, an olefin block copolymer, or a blend thereof, 30% to 50% by weight of an E / X / Y / Z epoxy-containing ethylene interpolymer, 0.5 to 5% by weight of a blowing agent, 0.1% to 1% by weight of an activator, and less than 0.05% by weight of a curing agent. The ethylene / alpha-olefin copolymer has a density of 0.840 g / cc to 0.910 g / cc and a melt index (I2) of 0.5 to 12.0 g / 10 min. The olefin block copolymer has a density of 0.860 g / cc to 0.890 g / cc and a melt index (I2) of 0.5 to 12.0 g / 10 min. In the E / X / Y / Z epoxy-containing interpolymer, E is an ethylene monomer comprising greater than 50 weight percent interpolymer, X is a (meth)acrylate, alkyl (meth)acrylate, or vinyl acetate comprising 0-40 weight percent interpolymer, Y is glycidyl methacrylate comprising 0.5-13 weight percent interpolymer, and Z is a copolymer unit derived from a comonomer selected from the group consisting of carbon monoxide, sulfur dioxide, and acrylonitrile comprising 0-10 weight percent interpolymer. [Brief description of the drawings]
[0006] [Figure 1A] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example A after foaming.
[0007] [Figure 1B] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example B after foaming.
[0008] [Figure 1C] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example C after foaming.
[0009] [Figure 1D] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example D after foaming.
[0010] [Figure 1E] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example E after foaming.
[0011] [Figure 1F] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example B after aging at 80° C. for 2 hours.
[0012] [Figure 1G] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example C after aging at 125° C. for 2 hours.
[0013] [Figure 1H] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example D after aging at 125° C. for 2 hours.
[0014] [Figure 1I] 1 shows a scanning electron microscope (SEM) image of the foam of Comparative Example E after aging at 125° C. for 2 hours.
[0015] [Figure 2A] 1 shows a scanning electron microscope (SEM) image of the foam of Example 1 prepared according to one or more embodiments shown and described herein after foaming.
[0016] [Figure 2B] 1 shows a scanning electron microscope (SEM) image of the foam of Example 2 prepared according to one or more embodiments shown and described herein after foaming.
[0017] [Figure 2C] 1 shows a scanning electron microscope (SEM) image of the foam of Example 3 prepared according to one or more embodiments shown and described herein after foaming.
[0018] [Figure 2D] 1 shows a scanning electron microscope (SEM) image of the foam of Example 4 prepared according to one or more embodiments shown and described herein after foaming.
[0019] [Figure 2E] 1 shows a scanning electron microscope (SEM) image of the foam of Example 1 prepared according to one or more embodiments shown and described herein after aging at 150° C. for 2 hours.
[0020] [Figure 2F] 1 shows a scanning electron microscope (SEM) image of the Example 2 foam prepared according to one or more embodiments shown and described herein after aging at 150° C. for 2 hours.
[0021] [Figure 2G] FIG. 2 shows a scanning electron microscope (SEM) image of the foam of Example 3 prepared according to one or more embodiments shown and described herein after aging at 150° C. for 2 hours.
[0022] [Figure 2H] FIG. 1 shows a scanning electron microscope (SEM) image of the foam of Example 4 prepared according to one or more embodiments shown and described herein after aging at 150° C. for 2 hours. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] In various embodiments described herein, a composition for forming a foam includes an ethylene / alpha-olefin copolymer, an olefin block copolymer, or a blend thereof, an E / X / Y / Z epoxy-containing ethylene interpolymer, a blowing agent, an activator, and less than 0.05 wt.% of a curing agent. Such embodiments allow for the formation of foams with good heat resistance and mechanical properties without the use of peroxides, as described in more detail below.
[0024] As used herein, the term "composition" and similar terms refer to a mixture of two or more substances, such as a polymer that has been blended with other polymers or that contains additives, fillers, etc. Pre-reaction mixtures, reaction mixtures, and post-reaction mixtures are included in the composition, the latter of which include reaction products and by-products, if any, as well as unreacted components of the reaction mixture and decomposition products formed from one or more components of the pre-reaction mixture or reaction mixture.
[0025] "Polymer" refers to a compound prepared by polymerizing monomers, whether they are the same or different types of monomers. Thus, the generic term polymer includes the term homopolymer, which is usually used to refer to a polymer prepared from only one type of monomer, and the term interpolymer, as defined below. The term polymer also includes all forms of interpolymers, such as random, block, etc. The terms "ethylene / alpha-olefin polymer" and "propylene / alpha-olefin polymer" refer to interpolymers, as described below. It is noted that polymers are often referred to as "made of" monomers, "based on" a particular monomer or type of monomer, or "containing" a particular monomer content, but it is understood that this refers to the polymerized remains of the particular monomer, and not the unpolymerized species.
[0026] "Interpolymer" means a polymer prepared by the polymerization of at least two different monomers. This general term includes copolymers, which are typically used to refer to polymers prepared from two or more different monomers, and includes polymers prepared from two or more different monomers, such as terpolymers, tetrapolymers, etc.
[0027] "Polyolefin", "polyolefin polymer", "polyolefin resin" and similar terms refer to simple olefins (of general formula C n H 2nPolyolefins refer to polymers made with monomers such as olefins (also called alkenes having the formula: ##STR00011##). Polyethylene is made by polymerizing ethylene with or without one or more comonomers, polypropylene is made by polymerizing propylene with or without one or more comonomers, etc. Thus, polyolefins include interpolymers such as ethylene-alpha-olefin copolymers, propylene-alpha-olefin copolymers, etc.
[0028] "(Meth)acrylic acid" includes methacrylic acid and / or acrylic acid, and "(meth)acrylate" includes methacrylate and / or acrylate.
[0029] "Calendaring" and similar terms, in the context of the various embodiments described herein, means the mechanical process by which molten polymer is converted into a sheet by passing it through a series of rollers, which coalesce, flatten and smooth the polymer into a sheet or film.
[0030] "Laminating" and similar terms typically refer to a process in which a film of plastic or similar material is applied to a substrate, which may be another film. The film may be applied to the substrate with or without an adhesive. In the absence of an adhesive, the film and / or substrate may be heated to facilitate thermal or melt lamination. Laminations are the product of laminating processes, and these products are multi-layered, i.e., they include at least two layers, a film layer in contact with a base or substrate layer.
[0031] "Foam" and similar terms mean a material formed by trapping many gas bubbles in a liquid or solid.
[0032] Various embodiments described herein include at least 50%, or from 50% to 99% by weight, based on composition, of ethylene / alpha-olefin copolymer, olefin block copolymer, or blends thereof.
[0033] The term "ethylene / alpha-olefin copolymer" generally refers to a polymer comprising ethylene and an alpha-olefin comonomer having 3 or more carbon atoms. In an embodiment, ethylene comprises the majority mole fraction of the whole polymer, i.e., ethylene comprises at least 50 mole percent (mol%) of the whole polymer. For example, ethylene may comprise at least 60 mol%, at least 70 mol%, or at least 80 mol%, with a substantial remainder of the whole polymer comprising at least one other comonomer that is an alpha-olefin having 3 or more carbon atoms. For many ethylene / octene copolymers, the composition may comprise an ethylene content of greater than 80 mol% of the whole polymer and an octene content of 10 mol% to 20 mol% or 15 mol% to 20 mol% of the whole polymer.
[0034] In various embodiments, the olefin block copolymer is, for example, an ethylene / alpha-olefin block copolymer. Commercially available examples of ethylene / alpha-olefin block copolymers include resins available under the trade name INFUSE™ available from The Dow Chemical Company (Midland, MI).
[0035] In various embodiments, the ethylene / alpha-olefin copolymer may comprise ethylene in polymerized form and one or more copolymerizable alpha-olefin monomers, characterized by multiple blocks or segments of two or more polymerized monomer units with different chemical or physical properties. The polyolefin elastomer may be a multi-block copolymer. In one or more embodiments, the multi-block copolymer may be represented by the formula (AB)n, where n is an integer of at least 1, preferably greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, or more, and "A" represents a hard block and "B" represents a soft block. In embodiments, A and B are linked in a substantially linear fashion, as opposed to a substantially branched or substantially star-shaped fashion. In one or more embodiments, the A and B blocks are randomly distributed along the polymer chain and do not have a structure such as the following: AAA-AA-BBB-BB. In some embodiments, the block copolymer does not have a third type of block comprising a different comonomer. In embodiments, block A and block B each have monomers or comonomers substantially randomly distributed within the block such that neither block A nor block B comprises two or more subsegments of distinct composition, such as tip segments, having a substantially different composition than the remainder of the block.
[0036] Ethylene / alpha-olefin block copolymers can include various amounts of "hard" and "soft" blocks. A "hard" block refers to a block of polymerized units in which ethylene is present in an amount greater than about 95% by weight, and preferably greater than about 98% by weight, based on the weight of the polymer. In other words, the comonomer content in the hard block, i.e., the content of monomers other than ethylene, is less than about 5% by weight, and preferably less than about 2% by weight, based on the weight of the polymer. In one or more embodiments, the hard block contains all or substantially all ethylene. A "soft" block, on the other hand, refers to a block of polymerized units in which the comonomer content, i.e., the content of monomers other than ethylene, is greater than about 5% by weight. For example, the comonomer content can be greater than about 5% by weight, greater than about 8% by weight, greater than about 10% by weight, or greater than about 15% by weight, based on the weight of the polymer. In various embodiments, the comonomer content in the soft blocks can be greater than about 20% by weight, greater than about 25% by weight, greater than about 30% by weight, greater than about 35% by weight, greater than about 40% by weight, greater than about 45% by weight, greater than about 50% by weight, or greater than about 60% by weight based on the weight of the polymer.
[0037] In various embodiments, the soft block is present in the ethylene / alpha-olefin block copolymer in an amount of about 1% to about 99% by weight of the total weight of the polyolefin elastomer. For example, the soft block may be present in the ethylene / alpha-olefin block copolymer in an amount of about 5% to about 95% by weight, about 10% to about 90% by weight, about 15% to about 85% by weight, about 20% to about 80% by weight, about 25% to about 75% by weight, about 30% to about 70% by weight, about 35% to about 65% by weight, about 40% to about 60% by weight, or about 45% to about 55% by weight of the total weight of the ethylene / alpha-olefin block copolymer. Conversely, the hard block may be present in a similar range. The weight percentages of the soft block and the hard block may be calculated based on data obtained from DSC or NMR. Such methods and calculations are disclosed in U.S. Patent Application Publication No. 2006 / 0199930.
[0038] Examples of alpha-olefin comonomers that can be used to form ethylene / alpha-olefin block copolymers include, by way of example and not limitation, propylene, isobutylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecent, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 4,6-dimethyle-1-heptene, 4-vinylcyclohexene, vinylcyclohexane, norbornadiene, ethylidenenorbornene, cyclopentene, cyclohexene, dicyclopentadiene, cyclooctene, C4-C6 40 Dienes, other C4-C 40 In further embodiments, the alpha-olefin comonomer may include a C4-C8 comonomer. Comonomer content can be determined using any suitable technique, such as techniques based on nuclear magnetic resonance ("NMR") spectroscopy, for example, as described in U.S. Pat. No. 7,498,282, which is incorporated herein by reference. 13 It can be measured by C NMR analysis.
[0039] In various embodiments, the ethylene / alpha-olefin block copolymers have a melt index (I2) of about 0.5 to about 30.0 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg). For example, the ethylene / alpha-olefin block copolymers can have a melt index (I2) of 0.5 to 30.0 g / 10 min, 0.5 to 12 g / 10 min, 0.5 g / 10 min to 5.0 g / 10 min, or 3.0 g / 10 min to 7.0 g / 10 min.
[0040] In various embodiments, the ethylene / alpha-olefin block copolymer has a density of 0.850 g / cc to 0.890 g / cc. All individual values and subranges from 0.850 g / cc to 0.890 g / cc are included herein and disclosed herein, and all individual values and subranges from 0.850 g / cc to 0.890 g / cc are included herein and disclosed herein, for example, the density of the ethylene / alpha-olefin block copolymer can be from a lower limit of 0.850 g / cc, 0.855 g / cc, 0.860 g / cc, 0.865 g / cc, or 0.870 g / cc to an upper limit of 0.890 g / cc, 0.885 g / cc, 0.880 g / cc, or 0.875 g / cc. In an embodiment, the ethylene / alpha-olefin block copolymer has a density of 0.860 g / cc to 0.890 g / cc.
[0041] Ethylene / alpha-olefin block copolymers have a melting temperature (T m ) (DSC). All individual values and subranges from 115°C to 125°C are included herein and disclosed herein, for example, the melting point of the ethylene / alpha-olefin block copolymer can be from a lower limit of 115°C, 116°C, 117°C, 118°C, 119°C, or 120°C to an upper limit of 125°C, 124°C, 123°C, 122°C, or 121°C.
[0042] In some embodiments, the ethylene / alpha-olefin block copolymers have a molecular weight distribution (MWD) of 3.5 or less. Molecular weight distribution (MWD) is defined as the weight average molecular weight (Mw) divided by the number average molecular weight (Mn). For example, the ethylene / alpha-olefin block copolymers of some embodiments have an MWD of 2 to 3. Techniques for determining molecular weight (Mn and Mw) and MWD can be found in U.S. Pat. No. 4,540,753, which is incorporated herein by reference.
[0043] The ethylene / alpha-olefin block copolymers can be formed utilizing known polymerization processes, such as those described in PCT Application Nos. PCT / US2005 / 008915, PCT Application Nos. PCT / US2005 / 008916, and PCT Application Nos. PCT / US2005 / 008917, each of which is incorporated herein by reference.
[0044] Additionally or alternatively, various embodiments include ethylene / alpha-olefin copolymers, such as homogeneously branched ethylene / alpha-olefin copolymers. These copolymers can be produced with single-site catalysts, such as metallocene catalysts or constrained geometry catalysts, and typically have melting points below 105° C., below 90° C., below 85° C., below 80° C., or below 75° C. The melting points are measured by differential scanning calorimetry (DSC), for example, as described in U.S. Pat. No. 5,783,638. In embodiments, the alpha-olefins are C3-C6, as described above. 20 It may be a linear, branched, or cyclic alpha-olefin.
[0045] Exemplary homogeneously branched ethylene-alpha-olefin copolymers include ethylene / propylene, ethylene / butene, ethylene / 1-hexene, ethylene / 1-octene, ethylene / styrene, etc. Exemplary terpolymers include ethylene / propylene / 1-octene, ethylene / propylene / butene, ethylene / butene / 1-octene, and ethylene / butene / styrene. The copolymers may be random copolymers.
[0046] In various embodiments, the ethylene / alpha-olefin copolymers have a melt index (I2) of about 0.5 to about 30.0 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg). For example, the ethylene / alpha-olefin copolymers can have a melt index (I2) of 0.5 to 30.0 g / 10 min, 0.5 to 12 g / 10 min, 0.5 g / 10 min to 5.0 g / 10 min, or 3.0 g / 10 min to 7.0 g / 10 min.
[0047] In various embodiments, the ethylene / alpha-olefin copolymer has a density from 0.840 g / cc to 0.910 g / cc, all individual values and subranges between 0.840 g / cc and 0.910 g / cc are included herein and disclosed herein, for example, the density of the ethylene / alpha-olefin block copolymer can be from a lower limit of 0.840 g / cc, 0.845 g / cc, 0.850 g / cc, 0.855 g / cc, 0.860 g / cc, 0.865 g / cc, or 0.870 g / cc to an upper limit of 0.910 g / cc, 0.905 g / cc, 0.900 g / cc, 0.895 g / cc, 0.890 g / cc, 0.885 g / cc, 0.880 g / cc, or 0.875 g / cc. In an embodiment, the ethylene / alpha-olefin copolymer has a density from 0.860 g / cc to 0.900 g / cc or from 0.860 g / cc to 0.890 g / cc.
[0048] Examples of commercially available homogeneously branched ethylene / alpha-olefin copolymers include homogeneously branched linear ethylene / alpha-olefin copolymers (e.g., those available under the trade names TAFMER™ from Mitsui and EXACT™ from Exxon Mobil Chemical Company), and homogeneously branched substantially linear ethylene / alpha-olefin polymers (e.g., those available under the trade names AFFINITY™ and ENGAGE™ polyethylene from The Dow Chemical Company, Midland, MI).
[0049] In various embodiments, the composition further comprises 30 wt% to 50 wt% of an E / X / Y / Z epoxy-containing ethylene interpolymer, where E is an ethylene monomer, X is a (meth)acrylate, an alkyl (meth)acrylate, or a vinyl acetate, Y is glycidyl methacrylate (GMA), and Z is a copolymer unit derived from a comonomer selected from the group consisting of carbon monoxide, sulfur dioxide, and acrylonitrile, and the E / X / Y / Z epoxy-containing ethylene interpolymer comprises 0 to 10 wt% of the interpolymer, based on the total weight of the composition. As used herein, "epoxy-containing ethylene interpolymer" refers to a first embodiment in which the epoxy composition can be copolymerized with ethylene through an epoxy-containing monomer, such as GMA, to the interpolymer backbone. In addition, "epoxy-containing ethylene interpolymer" can include a second embodiment in which the epoxy is grafted onto the interpolymer backbone. Furthermore, "epoxy-containing ethylene interpolymer" can include a combination of the first and second embodiments.
[0050] Ethylene can be present in an amount of more than 50% by weight, based on the total weight of polymerizable monomers. For example, the epoxy-containing ethylene interpolymer can include 50% to 99.5% by weight ethylene, 55% to 94% by weight ethylene, 60% to 90% by weight ethylene, or 65% to 85% by weight ethylene. All individual values and subranges between 50% and 99.5% by weight are included.
[0051] In embodiments, the X component can be present in an amount of 0% to 40% by weight, based on the total weight of polymerizable monomers. For example, the X component can be present in an amount of 1% to 40% by weight, 12% to 32% by weight, or 13% to 31% by weight, based on the total weight of polymerizable monomers. All individual values and subranges between 0% and 40% by weight are included. In embodiments, X is a copolymer unit -(CHCR 1 R 2 In some embodiments, R 1can be hydrogen, methyl, or ethyl. In some embodiments, R 2 is a carboalkoxy, acyloxy, or alkoxy of 1 to 10 carbon atoms. As noted above, in various embodiments, X is a (meth)acrylate, alkyl (meth)acrylate, or vinyl acetate. Suitable acrylate comonomers include methyl acrylate (MA), ethyl acrylate (EA), and butyl acrylate (BA).
[0052] In an embodiment, Y is a copolymer unit -(CHCR 3 R 4 In some embodiments, R 3 can be hydrogen or methyl. In some embodiments, R 4 can be carboglycidoxy or glycidoxy. In some embodiments, Y can be selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, glycidyl butyl acrylate, glycidyl vinyl ether, and combinations of two or more of glycidyl acrylate, glycidyl methacrylate, glycidyl butyl acrylate, and glycidyl vinyl ether. The epoxy-containing ethylene interpolymer of various embodiments comprises 0.5 wt% to 13 wt%, or 5 wt% to 10 wt%, of glycidyl methacrylate (GMA), based on the total weight of polymerizable monomers. Without being bound by theory, it is believed that the epoxy monomers present in the GMA crosslink with the azo group of the blowing agent or the ammonia decomposition product of the blowing agent to produce a crosslinked foam that is resistant to foam expansion. In addition, it is believed that the crosslinking between GMA and the azo or ammonia groups can achieve a strongly crosslinked foam without the need for a peroxide crosslinking agent.
[0053] In embodiments, Z can be a copolymer unit derived from a comonomer including carbon monoxide, sulfur dioxide, acrylonitrile, or other monomer. In further embodiments, the epoxy-functionalized ethylene copolymer can include from about 0% to about 10% by weight Z, from about 0% to about 8% by weight Z, from about 0% to about 6% by weight Z, from about 0% to about 4% by weight Z, from about 0% to about 2% by weight Z, from about 2% to about 10% by weight Z, from about 2% to about 8% by weight Z, from about 2% to about 6% by weight Z, from about 2% to about 4% by weight Z, from about 4% to about 10% by weight Z, from about 4% to about 8% by weight Z, from about 4% to about 6% by weight Z, from about 6% to about 10% by weight Z, from about 6% to about 8% by weight Z, or from about 8% to about 10% by weight Z based on the total weight of polymerizable monomers.
[0054] It is contemplated that some embodiments comprise 0 wt% Z. In such embodiments, the epoxy-containing ethylene interpolymer may be referred to as an E / X / Y epoxy-containing ethylene interpolymer.
[0055] The epoxy-containing ethylene interpolymers can have a melt index (I2) of 4 to 20 g / 10 min, 4 to 15 g / 10 min, 4 to 12 g / 10 min, or 5 to 10 g / 10 min, as determined according to ASTM D1238 (190° C., 2.16 kg). Examples of commercially available copolymer resins that can be used in some embodiments include those available under the trade name ELVALOY™ available from The Dow Chemical Company (Midland, MI).
[0056] According to various embodiments, the composition further comprises a chemical blowing agent to generate porosity for forming a foam upon heating. The chemical blowing agent may comprise a nitrogen-containing composition that may crosslink with the epoxy groups of the epoxy-containing ethylene interpolymer. In general, the amount of blowing agent is an amount effective to generate fairly uniform cell size within the foam. In various embodiments, the blowing agent is present in an amount of 0.1% to 30%, 0.5% to 5%, or 1% to 3% by weight based on the total weight of the composition. In various embodiments, the blowing agent is a chemical blowing agent that decomposes during the foaming process to liberate a gas (e.g., an azo compound or other nitrogen-containing compound such as ammonia) to form the foam. One or more azo compounds or other nitrogen-containing compounds liberated by the chemical blowing agent react with the GMA of the epoxy-containing ethylene interpolymer to generate a crosslinked epoxy-containing ethylene interpolymer. As described above and below, this crosslinking allows for the generation of strong foams that are resistant to expansion without the use of peroxide crosslinking agents.
[0057] Chemical blowing agents include azobisisobutyronitrile (AIBN), azodicarbonamide, dinitroso-pentamethylene-tetramine, p-toluenesulfonylhydrazide, p,p'-oxy-bis(benzenesulfonylhydrazide), and combinations thereof. An exemplary azo compound is azodicarbonamide. Commercially available chemical blowing agents suitable for use include Azodicarbonamide AC3000 available from Haihong Chemical. The blowing agent may be a mixture of blowing agents or a mixture of blowing agents and activators to adjust the expansion-decomposition temperature and the foaming process.
[0058] In various embodiments, the composition used to produce the foam comprises 0.05% to 5%, 0.1% to 1%, or 0.2% to 0.4% by weight of an activator based on the total weight of the composition. The activator reduces the decomposition temperature / profile of the blowing agent. In various embodiments, the activator is a metal stearate, such as zinc stearate. In embodiments, the activator is one or more metal oxides, metal salts, or organometallic complexes, or combinations thereof. Examples of suitable activators include zinc oxide, magnesium oxide, zinc stearate, calcium stearate, iron stearate, or combinations thereof. Other examples of suitable activators include imidazoles, tertiary amines, Lewis acids, boron trifluoride, and other well-known catalysts suitable for use in epoxy-amine curing processes. Without wishing to be bound by theory, it is believed that the activator helps to regulate the temperature at which the blowing agent is activated to produce gas that foams the composition to the desired thickness and / or density reduction.
[0059] In various embodiments, the composition comprises less than 0.05 wt.% of a curing agent based on the total weight of the composition. The curing agent comprises one or more organic peroxides, including dialkyl peroxides, peroxyesters, peroxydicarbonates, peroxyketals, diacyl peroxides, or combinations of two or more thereof. Examples of peroxides include dicumyl peroxide, di(3,3,5-trimethylhexanoyl)peroxide, t-butyl peroxypivalate, t-butyl peroxyneodecanoate, di(§-butyl)peroxydicarbonate, t-amyl peroxyneodecanoate, 1,1-di-t-butylperoxy-3,3,5-trimethylcyclohexane, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tertiarybutylperoxy)hexane, 1,3-bis(tertiarybutylperoxyl-isopropyl)benzene, or combinations thereof. Commercially available curing agents include those available under the tradenames LUPEROX® from Arkema or TRIGONOX® from Akzo Nobel, however, in other embodiments, the composition does not contain a peroxide.
[0060] In various embodiments, the composition may optionally include mineral oils, such as paraffinic, naphthenic, and other hydrocarbon or synthetic oils. Such oils may be present in an amount of 0% to 40%, 0% to 30%, 0% to 20%, 0.05% to 40%, 0.05% to 30%, or 0.05% to 20% by weight based on the total weight of the composition. If included, the oils may be used to adjust the flexibility of the final product, such as artificial leather, including foam.
[0061] Other additives that may be present in the composition at 0% to 30%, 0.1% to 20%, or 0.1% to 12% by weight based on the total weight of the composition may include pigments (TiO2 and other compatible color pigments), excipients (e.g., talc, calcium carbonate, barium sulfate, and / or silicon dioxide), stabilizers (e.g., antioxidants, UV absorbers, and / or flame retardants), and processing aids (e.g., calcium stearate and / or barium stearate). Antioxidants may include those available under the tradenames IRGANOX™ from BASF, such as IRGANOX™ 1010, and IRGANOX™ 3114. UV absorbers may include those available under the tradenames TINUVIN™ from BASF, such as TINUVIN™ 622.
[0062] In various embodiments, foams are formed from the compositions by mixing the polymer with sufficient heat to melt the polymer, adding the remaining ingredients, including the activator, blowing agent, and any optional additives, to form a homogenous mixture, and then heating the mixture to a temperature sufficient to produce foam.
[0063] In various embodiments, the resulting foam has uniform closed foam cells with little or no coalescence / collapse, high foaming efficiency (e.g., foam expansion rate reaches over 700% when foamed at 230°C for 50 seconds), foaming window of 30 to 200 seconds at 210°C to 230°C, and excellent foam elasticity.
[0064] According to various embodiments, the foam has a cell size of less than about 400 μm. For example, in embodiments, the foam has a cell size of at least 100 μm to no more than 400 μm. However, other cell sizes are contemplated, including cells sized greater than 400 μm, depending on the particular application for which the foam is to be utilized. Thus, in some embodiments, the foam may have a microfoam structure with cells less than 100 μm. In some embodiments, the foam may have a nanofoam structure with cells less than 1 μm.
[0065] In various embodiments, the foam is used to make artificial leather. The artificial leather can be unsupported (e.g., for additional backing, i.e., for skin applications) or supported by its application to a base layer such as a fabric (i.e., for upholstered applications), and can be formed through a calendaring process or other processes known and used in the art. Suitable fabrics can be woven, nonwoven, knitted, twill, sweater fabric, and the like. In various embodiments, the foam composition is applied to a polymer layer to a desired thickness and / or density by any suitable method, such as spray coating, and heat is applied. The blowing agent in the foam composition, when activated, produces a gas or mixture of gases that induces foaming to produce a foam layer that includes a cellular structure.
[0066] The artificial leather thus obtained has excellent touch, appearance, and full hand, similar to natural leather, and also has excellent flexibility and surface strength.The artificial leather of various embodiments is useful as a leather or cover in the automotive field, including interior leather or cover materials of seats, instrument panels, console boxes, armrests, headrests, door trims, rear panels, pillar trims, sun visors, headliners, steering wheel covers, the field of sports goods, such as ball covers, sports shoe uppers, racket grips, sports tools and goods, bicycle, motorcycle, and tricycle saddles and handlebar grip materials covers, the field of housing and construction, such as furniture upholstery, wall decoration materials, tablecloths, placemats, coasters, the field of industrial parts, such as grips and hoses for power tools, and other fields, such as covers for materials for bags, briefcases, handbags, clothing, files, albums, toys, and molded articles. EXAMPLES
[0067] The following examples are provided to illustrate various embodiments, but are not intended to limit the scope of the claims. All parts and percentages are by weight unless otherwise indicated. Approximate properties, characters, parameters, etc. are provided below for various examples, comparative examples, and materials used in the examples and comparative examples. In addition, the description of the raw materials used in the examples is as follows:
[0068] ENGAGE™ 8200 is a homogeneously branched, substantially linear ethylene / alpha-olefin polymer having a density of 0.87 g / cc, as measured in accordance with ASTM D792, a melt index (I2) of 5.0 g / 10 min, as measured in accordance with ASTM D1238 at 190° C. / 2.16 kg, and a Shore A hardness of 66, as measured in accordance with ASTM D2240,10s, available from The Dow Chemical Company, Midland, Mich.;
[0069] DE2400.05 is a propylene / ethylene copolymer having a density of 0.866 g / cc, as measured according to ASTM D792, and a melt flow rate (MFR) of 2 g / 10 min, as measured according to ASTM D1238-03 at 230° C. / 2.16 kg, available from The Dow Chemical Company, Midland, Mich.;
[0070] INFUSE™ 9507 is an olefin block copolymer (OBC) having a density of 0.866 g / cc, as measured in accordance with ASTM D792, and a melt index (I2) of 5.0 g / 10 min, as measured in accordance with ASTM D1238 at 190° C. / 2.16 kg, available from The Dow Chemical Company, Midland, Mich.;
[0071] E / X / Y / Z-1 is an E / X / Y / Z epoxy-containing interpolymer having an nBA content of 21 wt.% and a GMA content of 9 wt.%, a melt index (I2) of 8.0 g / 10 min, as measured according to ASTM D1238 at 190° C. / 2.16 kg;
[0072] AC 3000 is an azodicarbonamide blowing agent available from Haihong Chemical,
[0073] The talc was SQ-1250 talc available from HaiCheng Shuiquan Mineral Products Co., Ltd (Liaoning, China) having a 1250 mesh diameter;
[0074] IRGANOX™ 168 and IRGANOX™ 1010 are antioxidants available from BASF;
[0075] TINUVIN™ 622 is a UV stabilizer available from BASF.
[0076] Nine foam compositions, Comparative Examples A-E and Examples 1-4, were prepared according to the formulations (provided in weight percent) in Table 1 below.
[0077] [Table 1]
[0078] Comparative Examples A-E and Examples 1-4 were prepared by adding the polymers (DE 2400.05, ENGAGE™ 8200, INFUSE™ 9507, and / or E / X / Y / Z-1) to a 350 mL mixing bowl of a Brabender mixer and mixing at a temperature of 150° C. After the polymer was completely melted, the remaining ingredients were added to the bowl and mixed for an additional 5 minutes. The mixed compositions were further compression molded at 150° C. into 0.5 mm thick sheets for use in foam testing.
[0079] To measure the foaming performance, the oven temperature was set at 210°C and a 30*30 mm 2 Test specimens were cut from the compression molded sheets. Each test specimen was supported by release paper. The specimens were placed in the oven by quickly opening the door, placing the specimen in the oven, and immediately closing the oven door. A timer was started and the specimens were removed from the oven after 180 seconds.
[0080] The foam cells of each specimen were characterized after foaming and before the samples were aged. To characterize the foam cells, samples were cut with a razor blade, mounted in a sample holder, and coated with Ir using an Emitech K575X coater. The current was set at 20 mA and the coating time was set at 60 seconds. The coated samples were imaged with a Nova 630 SEM and the morphology of the samples was investigated with a Nova Nano 630 SEM using an ETD detector at an accelerating voltage of 5 KV, a spot size of 5 inches, and a working distance of about 12 mm. The foam thickness and the average foam cell size before aging are reported in Table 2 as "initial" values. Images from the SEM after foaming are shown in Figures 1A-1E (Comparative Examples A-E, respectively) and Figures 2A-2D (Examples 1-4, respectively).
[0081] [Table 2]
[0082] The samples of Comparative Examples B-E and Examples 1-4 were then tested for heat resistance by placing them in an oven at various temperatures for 2 hours. In particular, heat resistance was tested at 80°C, 125°C, and 150°C, and the foam cells were re-characterized according to the method described above. The results are reported in Table 2. Images from SEM after aging are shown in Figures 1F-1I (Comparative Examples B-E, respectively) and Figures 2E-2H (Examples 1-4, respectively).
[0083] As shown in Table 2 and FIG. 1A, Comparative Example A, which contained a propylene / ethylene copolymer without the E / X / Y / Z epoxy-containing ethylene interpolymer, did not expand sufficiently and the foam cells collapsed.
[0084] Comparative Example B contained a homogeneously branched substantially linear ethylene / alpha-olefin polymer without the E / X / Y / Z epoxy-containing ethylene interpolymer. After aging at 80°C for 2 hours, the original foam cells (Figure 1B) disappeared and a clear shrinkage in thickness was observed (816 mm to 500 mm), as shown in Figure 1F. Without being bound by theory, this is believed to be because the aging temperature (80°C) was above the melting point of the polymer (about 60°C), causing the polymer to melt during the aging process.
[0085] Comparative Examples C, D, and E were aged at 125° C. for 2 hours. As shown in FIG. 1G (Comparative Example C), 1H (Comparative Example D), and Comparative Example 1I (Comparative Example E), the foam cells originally present in FIG. 1C (Comparative Example C), 1D (Comparative Example D), and 1E (Comparative Example E) disappeared. Shrinkage in the thickness of these foams was also observed. As with Comparative Example A, this is believed to be because the aging temperature (125° C.) was higher than the melting point of INFUSE™ OBC (120° C.), which constitutes the majority of the polymer of Comparative Example C and the polymer of Comparative Example E. Comparative Example D contained as the major component the homogeneously branched substantially linear ethylene / alpha-olefin polymer of Comparative Example A. Both Comparative Examples D and E contained a small amount of E / X / Y / Z epoxy-containing ethylene interpolymer, but not present in a sufficient amount to prevent foam cell collapse.
[0086] However, Examples 1-4, which contain E / X / Y / Z epoxy-containing ethylene interpolymers at higher loadings (35%-50%), show good retention of foam thickness and foam cell structure, indicating improved heat resistance of the formulations. The maintained foam cell structure after aging at 150° C. for 2 hours can be seen by comparing Figures 2E (Example 1), 2F (Example 2), 2G (Example 3), and 2H (Example 4) with the SEM images of the initial foam cell structure in Figures 2A (Example 1), 2B (Example 2), 2C (Example 3), and 2D (Example 4), respectively.
[0087] Thus, various embodiments herein provide crosslinked foams that exhibit improved heat resistance, especially above 150°C. The crosslinked foams of various embodiments include an ethylene / alpha-olefin copolymer, a reactive epoxy group functionalized interpolymer, a chemical blowing agent (such as an AZO blowing agent), and an activator. In particular, the epoxy-containing ethylene interpolymer is a crosslinked epoxy-containing ethylene interpolymer produced by reaction of glycidyl methacrylate in the interpolymer with azo or nitrogen-containing groups formed from decomposition of the blowing agent. Without being limited by theory, it is believed that the foam crosslinking provides improved stability by resisting foam collapse at high temperatures.
[0088] Moreover, it should be noted that terms such as "generally," "generally," and "typically" are not used herein to limit the scope of the claimed invention or to imply that a particular feature is critical, essential, or even essential to the structure or function of the claimed invention. Rather, these terms are merely intended to highlight alternative or additional features that may or may not be utilized in a particular embodiment of the present disclosure.
[0089] It will be apparent that modifications and variations are possible without departing from the scope of the present disclosure, as defined in the appended claims. More specifically, although certain aspects of the present disclosure have been identified herein as preferred or particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to those aspects. The present invention may include the following aspects. [1] 1. A foam formed from a composition, the composition comprising: Based on the composition, at least 50% by weight of the composition has a density of 0.840 g / cc to 0.910 g / cc and a melt index (I) of 0.5 to 12.0 g / 10 min. 2 ethylene / alpha-olefin copolymers having a density of 0.860 g / cc to 0.890 g / cc and a melt index (I 2 ), or a blend thereof; Based on said composition, 30% to 50% by weight of an E / X / Y / Z epoxy-containing ethylene interpolymer, E being an ethylene monomer and comprising greater than 50% by weight of said interpolymer, X being a (meth)acrylate, an alkyl (meth)acrylate, or a vinyl acetate and comprising 0 to 40% by weight of said interpolymer, Y being glycidyl methacrylate and comprising 0.5 to 13% by weight of said interpolymer, and Z being a copolymer unit derived from a comonomer selected from the group consisting of carbon monoxide, sulfur dioxide, and acrylonitrile and comprising 0 to 10% by weight of said interpolymer, said weight percentages being based on the total amount of polymerizable monomers; 0.5 to 5% by weight, based on the composition, of a chemical foaming agent; 0.1 to 1% by weight of an active agent, based on the composition; and less than 0.05% by weight, based on the composition, of a curing agent. [2] The foam according to [1], wherein X comprises 1 to 40 wt % of the interpolymer. [3] 3. The foam of either [1] or [2], wherein the chemical blowing agent decomposes to liberate one or more azo or nitrogen-containing compounds. [4] The foam of [3], wherein the epoxy-containing ethylene interpolymer is a crosslinked epoxy-containing ethylene interpolymer produced by reaction of the glycidyl methacrylate with the one or more azo- or nitrogen-containing compounds liberated by the chemical blowing agent. [5] The foam according to any one of [1] to [4], wherein the chemical foaming agent is azodicarbonamide. [6] The foam according to any one of [1] to [5], wherein the activator is a metal stearate. [7] The foam according to [6], wherein the metal stearate is zinc stearate. [8] The ethylene / alpha-olefin copolymer, the olefin block copolymer, or both, are made of ethylene and C 4 ~C 8 The foam according to any one of [1] to [7], which is a copolymer of an alpha-olefin comonomer. [9] Said C 4 ~C 8 [8] The foam according to [8], wherein the alpha-olefin comonomer is octene.
[10] The foam according to any one of [1] to [9], wherein the ethylene / alpha-olefin copolymer, the olefin block copolymer, or both, have a density of 0.860 g / cc to 0.890 g / cc.
[11] The ethylene / alpha-olefin copolymer, the olefin block copolymer, or both have a melt index (I 2 The foam according to any one of [1] to
[10] ,
[12] The foam according to any one of [1] to
[11] , wherein the composition does not contain a peroxide.
[13] The foam according to any one of [1] to
[12] , wherein the composition further contains at least one mineral oil.
[14] An artificial leather comprising two or more layers, one of which is the foam according to any one of [1] to
[13] .
Claims
1. 1. A foam formed from a composition, the composition comprising: Based on the composition, at least 50% by weight of the composition has a density of 0.840 g / cc to 0.910 g / cc and a melt index (I) of 0.5 to 12.0 g / 10 min. 2 ethylene / alpha-olefin copolymers having a density of 0.860 g / cc to 0.890 g / cc and a melt index (I) of 0.5 to 12.0 g / 10 min; 2 ), or a blend thereof; Based on said composition, 30% to 49.4% by weight of an E / X / Y / Z epoxy-containing ethylene interpolymer, where E is an ethylene monomer and is present in an amount greater than 50% by weight based on the total amount of polymerizable monomers in the interpolymer, X is a (meth)acrylate, an alkyl (meth)acrylate, or a vinyl acetate and is present in an amount of 0 to 40% by weight based on the total amount of polymerizable monomers in the interpolymer, Y is glycidyl methacrylate and is present in an amount of 0.5 to 13% by weight based on the total amount of polymerizable monomers in the interpolymer, and Z is a copolymer unit derived from a comonomer selected from the group consisting of carbon monoxide, sulfur dioxide, and acrylonitrile and is present in an amount of 0 to 10% by weight based on the total amount of polymerizable monomers in the interpolymer; 0.5 to 5 weight percent, based on the composition, of a chemical blowing agent; 0.1 to 1% by weight, based on the composition, of an active agent; and less than 0.05% by weight, based on the composition, of a curing agent.
2. The foam of claim 1 comprising 1 to 40 weight percent X, based on the total amount of polymerizable monomers in the interpolymer.
3. 3. The foam of claim 1 or 2, wherein the chemical blowing agent decomposes to liberate one or more azo or nitrogen-containing compounds.
4. 4. The foam of claim 3, wherein the epoxy-containing ethylene interpolymer is a crosslinked epoxy-containing ethylene interpolymer produced by reaction of the glycidyl methacrylate with the one or more azo or nitrogen-containing compounds liberated by the chemical blowing agent.
5. The foam according to any one of claims 1 to 4, wherein the chemical blowing agent is azodicarbonamide.
6. The foam of any one of claims 1 to 5, wherein the activator is a metal stearate.
7. 7. The foam of claim 6, wherein the metal stearate is zinc stearate.
8. The ethylene / alpha-olefin copolymer, the olefin block copolymer, or both, are made of ethylene and C 4 ~C 8 The foam of any of claims 1 to 7 which is a copolymer of an alpha-olefin comonomer.
9. Said C 4 ~C 8 The foam of claim 8, wherein the alpha-olefin comonomer is octene.
10. The foam of any of claims 1 to 9, wherein the ethylene / alpha-olefin copolymer, the olefin block copolymer, or both, have a density from 0.860 g / cc to 0.890 g / cc.
11. The ethylene / alpha-olefin copolymer, the olefin block copolymer, or both have a melt index (I 2 The foam according to any one of claims 1 to 10, wherein
12. The foam of any one of claims 1 to 11, wherein the composition is peroxide-free.
13. The foam of any of claims 1 to 12, wherein the composition further comprises at least one mineral oil.
14. An artificial leather comprising two or more layers, one of which is the foam according to any one of claims 1 to 13.
Citation Information
Patent Citations
Ethylene polymer mixture
JP1988305144A
Crosslinked foams of ethylene vinyl acetate copolymers and acid copolymers
JP2003504439A
Multi-segment expandable polymer composition with controllable expansion direction
JP2010500451A
Crosslinked epoxy-containing ethylene interpolymer foam
JP2023508932A
New approach to heat expandable materials
US20190276624A1